Understanding of Weil's disease among canoeists. Issue 4 (December 1992) - Philipp, R; King, C; Hughes, A
Abstract : Although the risks of contracting Weil's disease in the UK are small, it can be a serious illness. Recently the disease has attracted public interest. This interest has prompted confusion and anxiety among recreational water user groups such as canoeists who had not previously seen themselves as being particularly at risk. In this paper, the experience of symptoms associated with Weil's disease among canoeists, their understanding and perceptions of the disease, and their compliance with preventive advice on the British Canoe Union (BCU) warning card, have been studied. Gaps in understanding and of adherence to preventive advice were identified. Accordingly, it was concluded that health education for canoeists could be improved. Consideration is being given by the BCU to the value of preparing a canoeist instructors' training pack.